Effect of oligosaccharides from agricultural waste as prebiotic in animal feed - Saenphoom, P.; Chimtong, S.; Poommarin, P.; Chaokaur, A. (International Journal of Agricultural Technology, 2024)
This study investigated the effects of oligosaccharide derived from sugar palm peel, coconut meal and spent tea as prebiotic for animal feed. The chemical compositions were significantly different between treatments (P<0.05). Enzyme-treated cashew nut testa and coconut meal had lower crude fiber and higher gross energy than other agricultural wastes. Furthermore, reducing sugar contents were significantly different between treatments (P<0.05). Enzyme-treated sugar palm peel had higher amount of reducing sugar than other agricultural waste. Oligosaccharides were analysis by thin-layer chromatography (TLC) found that all treatments resulted in the release of oligosaccharides. The results revealed that the sugar product from all experimental treatments could increase the growth of Lactobacillus plantarum except the enzyme-treated Brewer’s grain and spent tea leaves. Besides, enzyme-treated sugar palm peel, coconut meal and cashew nut testa could decreased the growth of Escherichai coli (500 µg/ml for 24 hrs). In summary, it was advised that enzyme-treated sugar palm peel, coconut meal and cashew nut testa can be used as prebiotics and antimicrobial agents. Enzyme-treated spent tea leaves can be used as only prebiotics. However, enzyme treated Brewer’s grain cannot be used as prebiotics and antimicrobial agents